2018
DOI: 10.1016/j.foodchem.2018.04.125
|View full text |Cite
|
Sign up to set email alerts
|

The impact of steeping, germination and hydrothermal processing of wheat (Triticum aestivum L.) grains on phytate hydrolysis and the distribution, speciation and bio-accessibility of iron and zinc elements

Abstract: Chelation of iron and zinc in wheat as phytates lowers their bio-accessibility. Steeping and germination (15 °C, 120 h) lowered phytate content from 0.96% to only 0.81% of initial dry matter. A multifactorial experiment in which (steeped/germinated) wheat was subjected to different time (2-24 h), temperature (20-80 °C) and pH (2.0-8.0) conditions showed that hydrothermal processing of germinated (15 °C, 120 h) wheat at 50 °C and pH 3.8 for 24 h reduced phytate content by 95%. X-ray absorption near-edge structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 39 publications
2
56
1
1
Order By: Relevance
“…Lemmens et al. () found that Zn was also detected in the pericarp tissues after sprouting, but it especially accumulates in the developing coleoptile and radicle, suggesting that Zn ions play a key role in their meristemic tissues (Ozturk et al., ).…”
Section: Biochemical and Physicochemical Changes In Cereal Grains As mentioning
confidence: 99%
See 3 more Smart Citations
“…Lemmens et al. () found that Zn was also detected in the pericarp tissues after sprouting, but it especially accumulates in the developing coleoptile and radicle, suggesting that Zn ions play a key role in their meristemic tissues (Ozturk et al., ).…”
Section: Biochemical and Physicochemical Changes In Cereal Grains As mentioning
confidence: 99%
“…While the outcomes of such studies are rather diverse, it can be concluded that a decrease in phytate content leads to a significant increase in mineral bioaccessibility. A 15% decrease in phytate content in wheat as a result of sprouting has been found to lead to an increase in Fe and Zn bioaccessibility from 4.6% to 14.1% and from 2.5% to 14.6%, respectively (Lemmens et al., ). A 30% decrease in phytate content in sorghum as a result of sprouting has been found to increase the Fe and Zn bioaccessibilities from 10% to 20% and from 8% to 15%, respectively (Afify et al., ).…”
Section: Biochemical and Physicochemical Changes In Cereal Grains As mentioning
confidence: 99%
See 2 more Smart Citations
“…Such results are expected and are in agreement with those of Pongrac et al In this study, the use of water with high zinc content increased wheat sprout zinc content (+232.9%). Moreover, the increase in zinc content might be related to the evolution of phytates after sprouting: In fact, a previous study of Lemmens et al showed an increase in phytase activity exceeding 3‐fold in wheat germinated for 48 h. Consequently, a decrease in phytate content is recorded and more zinc ions, previously chelated by phytates, are released. Luckily, the sprouting bioprocess also increases zinc bioaccessibility in wheat, as demonstrated previously …”
Section: Resultsmentioning
confidence: 99%